The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/2159-8290.cd-15-1434
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Calreticulin Requires Both Its Mutant C-terminus and the Thrombopoietin Receptor for Oncogenic Transformation

Abstract: Somatic mutations in calreticulin (CALR) are present in approximately 40% of patients with myeloproliferative neoplasms (MPN) but the mechanism by which mutant CALR is oncogenic remains unclear. Here, we demonstrate that expression of mutant CALR alone is sufficient to engender MPN in mice and recapitulates the disease phenotype of CALR-mutant MPN patients. We further show that the thrombopoietin receptor, MPL is required for mutant CALR-driven transformation through JAK-STAT pathway activation, thus rendering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
241
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(278 citation statements)
references
References 45 publications
30
241
0
1
Order By: Relevance
“…The effect of ruxolitinib on mice with CALR mutations also supports the idea that mutant CALR autonomously activates the JAK-STAT signaling cascade and induces sustained thrombocytosis with increased numbers of megakaryocytes. Our observations, together with previous reports [4][5][6][7], indicate that the CALR mutation is sufficient to augment megakaryocytic cell growth and cause ET, and that CALR mutations, like the JAK2 mutation, play a driver role in MPNs.…”
supporting
confidence: 82%
“…The effect of ruxolitinib on mice with CALR mutations also supports the idea that mutant CALR autonomously activates the JAK-STAT signaling cascade and induces sustained thrombocytosis with increased numbers of megakaryocytes. Our observations, together with previous reports [4][5][6][7], indicate that the CALR mutation is sufficient to augment megakaryocytic cell growth and cause ET, and that CALR mutations, like the JAK2 mutation, play a driver role in MPNs.…”
supporting
confidence: 82%
“…More recent studies further confirmed that patients with calreticulin or myeloproliferative leukemia virus oncogene (MPL) mutations, the other 2 major genetic abnormalities in Philadelphia-chromosome-negative MPNs (10), also involve activation of the JAK/STAT pathway (11). These reports underscore the JAK/STAT pathway in the pathogenesis of MPNs and as a valid target for therapy.…”
Section: Introductionmentioning
confidence: 83%
“…43 Differences in cytosolic calcium mobilization have been reported with the 52 base pair deletion, 44 suggesting that this may be one mechanism by which mutant CALR exerts its effect, and expression of the mutant protein does appear to be particularly restricted to megakaryocytes on immunohistochemical evaluation of bone marrow specimens. 45 More recently, it has been shown that CALR mutations can impart TPO-independence in both cell lines 46,47 and retroviral mouse models, 48,49 in a MPL-and JAK2-dependent manner, mimicking the effect of activating MPL mutations. This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%
“…45 More recently, it has been shown that CALR mutations can impart TPO-independence in both cell lines 46,47 and retroviral mouse models, 48,49 in a MPL-and JAK2-dependent manner, mimicking the effect of activating MPL mutations. This has been shown to be mediated by direct binding of MPL by the N domain of CALR, a phenomenon that uniquely occurs in the presence of the mutated C-terminus, 48,49 leading to autocrine activation of MPL, JAK2 dimerization and downstream STAT5 and ERK phosphorylation. 46,49 It is therefore clear that the inappropriate activation of JAK2 signaling is common to the three main phenotypic driver mutations (i.e., those in CALR, MPL and JAK2 itself) and plays an important role in disease pathogenesis in each case, in keeping with the clinical efficacy of JAK2 inhibition irrespective of the presence of the mutations in JAK2.…”
Section: Mutations In Mpl and Calrmentioning
confidence: 99%